Clinical impact of eliminating nonpulmonary vein triggers of atrial fibrillation and nonpulmonary vein premature atrial contractions at initial ablation for persistent atrial fibrillation. (18th December 2020) - Tohoku, Shota; Fukunaga, Masato; Nagashima, Michio; Korai, Kengo; Hirokami, Jun; Yamamoto, Kei; Takeo, Ayaka; Niu, Harushi; Ando, Kenji; Hiroshima, Kenichi
Abstract: Background: The role of nonpulmonary vein (PV) triggers ablation in persistent atrial fibrillation (PEAF) was suggested but it is still under debate. Objectives: We aimed to assess the effectiveness of non‐PV trigger‐targeted ablation for patients with PEAF. Methods: Consecutive patients with PEAF undergoing catheter ablation (CA) between January 2015 and April 2017 were enrolled. Isoproterenol plus adenosine challenge was performed to provoke non‐PV triggers. Non‐PV triggers were defined as the trigger beats inducing AF (non‐PV AF triggers) and/or frequent premature contractions (non‐PV PACs) from other than PVs. Three groups were defined: Group 1 ( n = 186) without non‐PV triggers; Group 2 ( n = 65) with non‐PV triggers that could be completely eliminated with CA; Group 3 ( n = 49) with non‐PV triggers still inducible after CA. The primary endpoint was freedom from any atrial tachyarrhythmia (ATa) recurrence. Results: A total of 300 patients (230 males, age 64 ± 10) were enrolled. The mean follow‐up period was 27 ± 10 months. Freedom from ATa recurrence at 1 and 2 years were significantly lower in Group 3 compared to the other two groups (Group 1; 74.7%, 67.2% vs. Group 2; 75.8%, 68.3% vs. Group 3: 52.1%, 38.6%, p = .0005), irrespective of the type of non‐PV triggers (non‐PV AF triggers vs. non‐PV PACs). On multivariate analysis, unsuccessful elimination of non‐PV triggers was an independent predictor for ATa recurrence (hazard ratio = 1.80, 95% confidence interval = 1.07–2.95, p = .026). Conclusion: Successful non‐PV triggers elimination can improve the ATa recurrence rate in PEAF ablation. ATa recurrence rate is higher, if non‐PV AF triggers or even non‐PV PACs remain in patients with PEAF.